Assessment of post-disaster reentry traffic in megaregions using agent-based simulation. (August 2019) - Zhang, Zhao; Wolshon, Brian; Herrera, Nelida; Parr, Scott
Highlights: This paper presents an agent-based simulation model to investigate the performance of traffic during post disaster reentry for the Gulf Coast megaregions. This research shows that reentry traffic processes behavior similar to, but in the reverse direction of evacuations. The heterogeneity of traffic flow distribution is the main reason that determines the network performance for any set of conditions. Prolonging departure time range would not always benefit the network performance and an acceptable departure time range will benefit the reentry process while not waste public resources. Abstract: Transportation personnel, assets, and systems play important roles during emergencies. Of particular note is the critical function of road networks as lifelines for evacuations, then, after such events, to facilitate the rapid inflow of support personnel and resources needed to assess and repair damage. They also provide access for the safe and rapid return of evacuees. Despite the importance of reentry and repopulation, the role of transportation systems for them has been a relatively lightly researched topic. This paper describes research to analyze the traffic processes associated with post-evacuation reentry and its associated travel time and delay. To examine the most extreme of conditions; this effort also focused on repopulation and reentry after mass evacuations in megaregions. Among the findings of this work were that, as expected, reentry traffic processes generally behave similar to, but in the reverse direction, of evacuations. However, contrary to commonly held belief, they are not identically opposite. Rather, network performance during reentry may often be better than that of evacuation. Another broad finding of the research was that the spatial heterogeneity of traffic distribution across available roadways is a primary factor in determining network performance, meaning the more uniform the spread of on all links, the more efficient the network will operate. A third significant finding of this research was also the importance of the temporal spreading of returnee departure times on network efficiency.